2007
DOI: 10.1021/jf070308a
|View full text |Cite
|
Sign up to set email alerts
|

Octanol−Water Partition Coefficients for Predicting the Effects of Tannins in Ruminant Nutrition

Abstract: Tannins can cause beneficial or harmful nutritional effects, but their great diversity has until now prevented a rational distinction between tannin structures and their nutritional responses. An attempt has been made to study this problem by examining the octanol-water solubilities of tannins. A relatively simple HPLC method has been developed for screening mixtures of plant tannins for their octanol-water partition coefficients (Kow coefficients). Tannins were isolated from the fruits and leaves of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 43 publications
2
40
0
Order By: Relevance
“…Measurement of log P ow of the main polyphenolic components revealed that PAs (log P ow from À1:00 to 0.10) were slightly more hydrophobic than the dimeric and trimeric ETs (log P ow from less than À3:0 to À2:0). Values for EC, 0.26 in the polyphenol fraction and 0.33 for the reference compound, were coincident with those reported by MuellerHarvey et al 21) As different polyphenolic profiles are extracted depending on the polarity of the extracting solvent, 25) a water-solvent biphasic partition system using several solvents with intermediate polarities (dielectric constants from 0 to 1) was examined for the separation of PAs and ETs. Respective partition between water and ethyl acetate (dielectric constant of 0.73) successfully yielded an ET fraction with no PAs and a PA fraction containing PAs (8.88%).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Measurement of log P ow of the main polyphenolic components revealed that PAs (log P ow from À1:00 to 0.10) were slightly more hydrophobic than the dimeric and trimeric ETs (log P ow from less than À3:0 to À2:0). Values for EC, 0.26 in the polyphenol fraction and 0.33 for the reference compound, were coincident with those reported by MuellerHarvey et al 21) As different polyphenolic profiles are extracted depending on the polarity of the extracting solvent, 25) a water-solvent biphasic partition system using several solvents with intermediate polarities (dielectric constants from 0 to 1) was examined for the separation of PAs and ETs. Respective partition between water and ethyl acetate (dielectric constant of 0.73) successfully yielded an ET fraction with no PAs and a PA fraction containing PAs (8.88%).…”
Section: Discussionsupporting
confidence: 85%
“…Octanol-water partitioning was carried out in a manner similar to the method of Mueller-Harvey et al 21) Aliquots of a polyphenol fraction from boysenberry seeds were added to a mixture of octanol and water. The octanol and water phases were separated after vigorously stirring for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction of procyanidins with proteins has been studied using several technical approaches (Baxter, Lilley, Haslam, & Williamson, 1997;Hagerman & Butler, 1981;Mueller-Harvey et al, 2007;Papadopoulou, Green, & Frazier, 2005). Present knowledge indicates that this interaction is affected by parameters of the protein (molecular size, hydrophobicity, structural flexibility), the polyphenol (degree of polymerisation, extent of galloylation, structural flexibility), and the environment (temperature, pH, ionic strength, presence of organic solvents and presence of carbohydrates) (Carvalho, Póvoas, Mateus, & de Freitas, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This confirms that sorption capacity is similar for polyphenols with similar polarities, across a wide range of smaller polyphenols and tannins including compounds from both major classes of tannins. It is important to note that the reported K ow values for tannins range from 10 -4 to 10 3 (Mueller-Harvey et al 2007). Given the importance of polarity in dictating sorption of tannins, and the wide range of polarities reported for polyphenols, it is clear that tannins cannot be considered as a single class of compounds with common sorption characteristics.…”
Section: Sorbed (Mg)mentioning
confidence: 99%
“…Procedures for extracting compounds from soils typically employ a single solvent in which polyphenols are generally soluble, such as methanol (Muscolo and Sidari 2006;Kuiters and Denneman 1987;Cecchi et al 2004). Given the wide range of polarities of natural polyphenols (Frazier et al 2010;Mueller-Harvey et al 2007) and the importance of polarity in determining sorption to soil (see Table 1), we developed a novel extraction procedure that uses a series of solvents with differing polarities. We validated the method using soils amended with known amounts of defined polyphenols.…”
Section: Extractionmentioning
confidence: 99%